1995
DOI: 10.1002/kin.550270703
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the formation of N‐chloramines

Abstract: We studied the kinetics of the chlorination of amines by sodium hypochlorite in strongly alkaline aqueous solution. A reaction mechanism compatible with experimental results is proposed and discussed. o 1995

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 9 publications
3
25
1
Order By: Relevance
“…It was concluded from the observed pH reaction profiles that the acid (HOCl), rather than the hypochlorite anion ( − OCl), is more reactive, and that with Cys as the target, the thiol anion (RCH 2 S − ) is the more reactive species [49]. This group has also studied the reactions of HOCl with various amines at different pH values, and concluded that − OCl is more reactive than the acid (HOCl), and reacts most readily with protonated amine groups (RNH 3 + ) [47,48,77,79]. This results in maximal reaction rates at pH values that are the average of the pK a values for HOCl and the amine (usually pH ~ 8.5).…”
Section: Kinetics Of Hocl Reactionsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was concluded from the observed pH reaction profiles that the acid (HOCl), rather than the hypochlorite anion ( − OCl), is more reactive, and that with Cys as the target, the thiol anion (RCH 2 S − ) is the more reactive species [49]. This group has also studied the reactions of HOCl with various amines at different pH values, and concluded that − OCl is more reactive than the acid (HOCl), and reacts most readily with protonated amine groups (RNH 3 + ) [47,48,77,79]. This results in maximal reaction rates at pH values that are the average of the pK a values for HOCl and the amine (usually pH ~ 8.5).…”
Section: Kinetics Of Hocl Reactionsmentioning
confidence: 95%
“…The kinetics of reactions of HOCl with amino acid sidechains and other protein targets have been studied in some detail, both by competitive kinetic studies and stopped flow methods [13,47,49,54,57,[75][76][77][78]. Many of the early studies of HOCl reaction kinetics focused on amine groups, particularly the simplest amine, ammonia, and were undertaken in acidic (pH 2.5-6) or basic (pH [10][11][12][13] solutions.…”
Section: Kinetics Of Hocl Reactionsmentioning
confidence: 99%
“…With GlcNH 2 (1-5 mM; 1 mM HOCl) under analogous conditions, a rapid loss of the − OCl peak (within 30 s) and formation of a peak with λ max 258 nm (Supplementary Figure 1E, inset, at http://www.BiochemJ.org/bj/391/bj3910125add.htm) were detected. Rate constants for reaction at 22 and 37 • C ( Table 2) were estimated using the Arrhenius equation with an activation energy (E a ) of 43 kJ · mol −1 ; the latter value is the experimentally determined E a for the reaction of HOCl with 2-propylamine [33], a close structural analogue of the GlcNH 2 -derived amine function. As the kinetic data obtained were limited by the dead time of the stopped-flow system at these temperatures, experiments were carried out at 9.5 • C to slow the reaction down.…”
Section: Rate Constants For Reaction Of Hocl With Glycosamine Monosacmentioning
confidence: 99%
“…Excellent correlations between rate constants and nucleophile basicity have previously been reported for the N-halogenation of amines and amino acids by sodium hypochlorite 6,7 or sodium hypobromite 14 and for several other chemically controlled reactions involving chloronium ion transfer, such as the reactions of chloramines with amines, amino acids and peptides 15,16 and the oxidation of iodide, 17 bromide, 18 cyanide, 19 nitrite 20 or sulphite 21 by hypochlorous acid or N-chloramines, which involve nucleophilic attack on the chlorine, followed by cleavage of the Cl-O bond and the loss of an OH group. In every case where the reaction is not diffusion controlled, the rate constant increases with increasing basicity of the amino group of the substrate.…”
Section: Mechanism and Discussionmentioning
confidence: 69%
“…This behaviour departs markedly from that of similar reactions where sodium hypochlorite was used as the halogenating reagent. 6,7 In order to clarify the mechanism of this type of reaction, in this work we carried out a kinetic study of the formation of N-chloro compounds by use of NCS as the halogenating reagent.…”
Section: Introductionmentioning
confidence: 99%